Nilton Hebling's career and contribution to carcinology - Negreiros-Fransozo, Maria Lucia [UNESP]; Fransozo, Adilson [UNESP] (Soc Brasileira Carcinologia, 2016)
This is a brief comment on Nilton Hebling's career and contribution to carcinology. Our intention is to show to next generation of carcinologists some insights of his professional life, and to acknowledge his great attitude while teaching and mentoring many Brazilian carcinologists.
Keywords: Scientific legacy; larval development; decapod; morphology